Ecology, genetic diversity, and population structure among commercial varieties and local landraces of Capsicum spp. grown in northeastern states of India - Verma, Veerendra Kumar; Pandey, Avinash; Thirugnanavel, Anbazhagan; Rymbai, Heiplanmi; Dutta, Niharika; Kumar, Amit; Bhutia, Tshering Lhamu; Jha, Anjani Kumar; Mishra, Vinay Kumar (Frontiers in Plant Science, 2024)
Northeastern states of India are known for unique landraces of Capsicum spp. with geographical indications. However, little information is available about these valuable landraces of chillies. Surveys and collections were carried out in niche areas to find out their ecology and diversity through morphological traits and molecular analysis using microsatellite markers. Our result characterised the ecology of niche areas as cool (11.0–20.70C) and humid (>60% relative humidity) climates for dalle-chilli (Capsicum annuum L.); mild-warm (12.2–28.60C) and humid for king-chilli (C. chinense Jacq.); and cool to warm (11.3-33.10C) and humid for bird's eye chilli (C. frutescens L.) during the crop period. The canonical correspondence analysis (CCA) has shown the significant impact of temperature on the agro-morphological traits and distribution of the landraces in their niche areas. A wide variability was observed for different quantitative traits and yield attributing characters (fruit length, diameter, weight, and yield), showing high heritability (97.0–99.0%), and genetic advance as a percentage of the mean (119.8–434.0%). Total 47 SSR markers used for the molecular analysis generated 230 alleles, ranging from 2 (HPMSE-7) to 10 (HPMSE-5), with an average of 4.89 alleles per locus. The average polymorphism information content was also high (0.61) and ranged from 0.20 (HPMSE-7) to 0.85 (CAMS-91). The observed average heterozygosity was lower than the expected value. Analysis of molecular variance has shown significant variation within (69%) and between (31%) of the populations of Capsicum spp. Based on Nei’s genetic distance, bird's eye chilli and king-chilli were found to be closer to each other, while dalle-chilli a tretraploid species, was closer to hot pepper (C. annuum). However, the flower size of dalle-chilli was large and found closer to king-chilli in colour and differs from C. chinense due to the presence of calyx teeth. For quality traits, landraces king-chilli, dalle-chilli, and bird’s eye chilli have shown 2.8, 2.0, and 1.4 times higher average capsaicin and 0.46, 0.25, and 0.22 times higher average oleoresin content over the hot pepper, respectively. The knowledge of ecology and diversity can be used in identifying new areas for production, selection of elite lines, conservation, and crop improvement.